Asked by  | 21st Sep, 2008, 08:05: AM

Expert Answer:

we know that i4=1 and i2=-1 and i3 = -i

using these relations

consider (1+i) (1+i3) = (1+i)(1-i) = 1-i2 = 1+1=2

so first two factors are equal to 2

if we consider next two factors (1+i5) (1+i7) = (1+i) (1+i3) = 2

every two factors when multiplied are equal to 2

so 2 multiplied by 2n/2 = n times = 2n

Answered by  | 21st Sep, 2008, 12:54: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.